War by other means geoeconomics and statecraft - Blackwill, Robert D.; Harris, Jennifer M. 1981- (The Belknap Press of Harvard University Press, 2016)
"A book about how nations use economic instruments to pursue geopolitical objectives. From Russia's coercive economic pressure on Ukraine, in Europe, and in Central Asia; to the steady sums of money that Gulf monarchies have extended to the Egyptian government following the ouster of President Morsi; to the varied economic retributions that China has dealt along its periphery amid tensions in the South and East China Seas--states are increasingly waging geopolitics with capital, attempting with sovereign checkbooks and other economic tools to achieve foreign policy objectives once the target of military coercion or conquest. For many countries, the theater of foreign policy engagement is predominantly markets. Today's leaders are as or more likely to air disagreements with foreign policies through restrictions on trade, or the buying and selling of debt, as through military activities. Not the United States. For Washington policymakers, vital national interests are still defined and pursued largely in political-military terms, a framework that sacrifices the power and potential of economics and finance as instruments of state purpose. This book aims to advance a comprehensive understanding of how states are applying economic instruments to advance geopolitical ends--a brand of statecraft the authors term geoeconomics--and what today's geoeconomic practices imply for how the United States in particular should think about and conduct its foreign affairs."--Provided by publisher.